A Systemic Review on Techniques of Solubility Enhancement for Poor Water-Soluble Drugs - Deshmukh, Dr. Prasad; Nimkar, Sangam; Phuse, Amruta; Ruikar, Dipti; Bonde, Dipti (Asian Journal of Pharmaceutical Research and Development, 2024)
Background Investigating novel methods to improve solubility in order to increase drug absorption along with improving pharmaceutical formulations. Main body of the abstractThe limited water solubility of active pharmaceutical ingredients constrains their pharmacological efficacy. However, the solubility parameter must not be compromised, necessitating the use of various strategies to improve their bioavailability. The solubility of drugs significantly impacts their pharmacokinetics, pharmacodynamics, as well as other characteristics like drug distribution, protein binding, and absorption. This review article aims to provide a concise overview of both traditional and innovative techniques employed to enhance the solubility of medications that have low solubility. These methods encompass several physical and chemical techniques, such as reducing particle size, creating solid dispersions, micronization using supercritical fluid technology, using cryogenic technology, utilizing complexation, employing hydrotrophy, employing crystal engineering, and developing solid self-emulsifying drug delivery systems. These various methods have contributed to improve the bioavailability of medications that are taken orally by enhancing the solubility of pharmaceuticals that have low water solubility. Short conclusion Thereview offers comprehensive insights into tactics for enhancing solubility, along with the significance of solubility and the most recent strategies for augmenting it.